Genomic Characterization of mcr-1-Carrying Foodborne Salmonella enterica serovar Typhimurium and Identification of a Transferable Plasmid Carrying mcr-1, blaCTX-M-14, qnrS2, and oqxAB Genes From Ready-to-Eat Pork Product in China - Li, Lili; Wan, Xiulin; Olsen, Rikke Heidemann; Xiao, Jian; Wang, Chong; Xu, Xuebin; Meng, Hecheng; Shi, Lei (Frontiers in Microbiology, 2022)
Salmonella enterica resistant to colistin, third-generation cephalosporins (3GCs) and fluoroquinolones (FQs) has been deemed a high-priority pathogen by the World Health Organization (WHO). The objective of this study was to characterize 11 mcr-1-harboring Salmonella enterica serovar Typhimurium isolates from raw pork and ready-to-eat (RTE) pork products in Guangzhou, China. All isolates were multi-drug resistant and contained 6-24 antibiotic resistant genes. The mcr-1 gene was in the most conserved structure (mcr-1-orf) in eight isolates, and in mobile structure (ISApl1-mcr-1-orf) in three isolates. One raw pork isolate SH16SF0850 co-harbored mcr-1, blaCTX-M-14 and oqxAB genes. One isolate 17Sal008 carrying mcr-1, blaCTX-M-14, qnrS2 and oqxAB genes located on a 298,622 bp IncHI2 plasmid pSal008 was obtained from a RTE pork product for the first time. The pSal008 was closely related to a plasmid in a S. Typhimurium isolate from a one-year old diarrhoeal outpatient in China and was found to be transferable to Escherichia coli J53 by conjugation. Genome sequence comparisons by cgMLST based on all S. Typhimurium isolates from China inferred highly probably epidemiological links between some pork isolates and no possible epidemiologically links between RTE pork isolate 17Sal008 with other isolates. Our findings indicated that raw pork and pork products are potential reservoirs of mcr-1-harboring S. Typhimurium and highlighted the necessary of continuous monitoring of colistin, 3GCs and FQs resistant S. Typhimurium from different origins.